The multifunctional RNA-binding protein hnRNPK is critical for the proliferation and differentiation of myoblasts - Xu, Yongjie (BMB Rep, 2018)
HnRNPK is a multifunctional protein that participates in chromatin remodeling, transcription, RNA splicing, mRNA stability and translation. Here, we uncovered the function of hnRNPK in regulating the proliferation and differentiation of myoblasts. hnRNPK was mutated in the C2C12 myoblast cell line using the CRISPR/Cas9 system. A decreased proliferation rate was observed in hnRNPK-mutated cells, suggesting an impaired proliferation phenotype. Furthermore, increased G2/M phase, decreased S phase and increased sub-G1 phase cells were detected in the hnRNPK-mutated cell lines. The expression analysis of key cell cycle regulators indicated mRNA of Cyclin A2 was significantly increased in the mutant myoblasts compared to the control cells, while Cyclin B1, Cdc25b and Cdc25c were decreased sharply. In addition to the myoblast proliferation defect, the mutant cells exhibited defect in myotube formation. The myotube formation marker, myosin heavy chain (MHC), was decreased sharply in hnRNPK-mutated cells compared to control myoblasts during differentiation. The deficiency in hnRNPK also resulted in the repression of Myog expression, a key myogenic regulator during differentiation. Together, our data demonstrate that hnRNPK is required for myoblast proliferation and differentiation and may be an essential regulator of myoblast function.